The role of extracellular proteases enzyme in bacterial adherence - Sarab Alshamaa (مجلة التربية والعلم, 2009)
Abstract : Extracellular proteases with caseinolytic activities were identified in culture supernatant of several pathogenic bacterial isolates of Staphylococcus aureus and Pseudomonas aeruginosa. Specific activities of these enzymes ranged from 0.27 to 3.89 unit/min/mg protein. The most virulent isolates with high level of proteases production revealed great adherence ability to epithelial cells isolated from mouth and adherence to the tubes surface while others without any level of production of these enzymes didn't posses adherence ability. This proved the correlation between the production of these enzymes and bacterial adherence ability. Extracellular proteases considered very important virulence factors because it was important invasion factors related to bacterial nutrition and metabolism.